Risk attitudes and human mobility during the COVID-19 pandemic - Ho Fai Chan; Ahmed Skali; David Savage; David Stadelmann; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2020)
Behavioural responses to pandemics are less shaped by actual mortality or hospitalization risks than they are by risk attitudes. We explore human mobility patterns as a measure of behavioural responses during the COVID-19 pandemic. Our results indicate a strong negative relationship between mobility reduction and risk-taking preferences. We find that the sharp decline in movement after the WHO (World Health Organization) declared COVID-19 to be a pandemic can be attributed to risk attitudes, especially for visits to places classified as retail and recreation, transit stations and workplaces. This suggests that individuals with risk-averse attitudes are more likely to adjust their behavioural activity in response to the declaration of a pandemic even prior to most official government lockdowns. We also find regions with higher risk aversion report a larger relative reduction in frequency of visits to places such as retail shops, grocery stores, parks, and public transport during the weekends compared to weekdays, whereas risk-loving regions are more likely to go to workplaces and less likely to stay at home during the weekends. There is also evidence to suggest that in areas with a larger share of older people in the population, risk-loving individuals are more likely to restrain themselves from taking public transport, engaging in non-essential retail shopping, going to workplaces, and staying home. Finally, we also find that the rate of behavioural adjustment, measured as the effect of mobility change after the first recorded death in the country, is sharper when the population have a larger risk pool population independent of government lockdowns.
Keywords: 330; Coronavirus; Risikopräferenz; Mobilität; Soziale Beziehungen; Welt